The use of the poem by Ka'b ibn Zuhayr by al-Nudhi - Saleh, Asst.L. Nadia Saadi; Mukhlif, Asst.L. Ruqaya Abdul Rahman (Sulaimani Journal for Humanities, 2024)
This research focuses on the emulation of a poetic text inherited from our ancestors, namely Ka'b ibn Zuhayr's Burda poem, which has been imitated by poets both ancient and modern, who have composed quintets and hemistichs in its form. This study attempts to analyze the poem by Sheikh al-Nawdahi, who composed a quintet based on Ka'b ibn Zuhayr's Burda. The analysis examines the artistic techniques employed to highlight the points of convergence and divergence between his poem and the Burda poem.
Keywords: AlNawdhi; poem; quintain; literary criticism; artistic use; Kab ibn Zuhayr; Banat Suad alBurda